Evaluation of Increasing Dietary Threonine to Lysine Ratio in Corn Soybean Meal Diets with and without DDGS on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs - Andres F. Tolosa; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 2,160 pigs (PIC 337 × 1050; initial BW 77.3 lb) were used in a 112-d growth trial to evaluate the effects of normal or high SID Thr:Lys ratio in diets with and without DDGS on growth performance. Pigs were randomly assigned to pens (27 pigs per pen) in a randomized complete block design by BW with 20 replications per treatment. Pens of pigs were allotted to 1 of 4 dietary treatments arranged in a 2 × 2 factorial with main effects of dietary Thr level (Normal vs. High) and DDGS (with or without DDGS). Treatment diets were formulated in 4 phases from 75 to 125, 125 to 175, 175 to 230, and 230 to 300 lb BW. Diets with high DDGS were formulated to include 40% DDGS in phase 1 and 2, 30% in phase 3, and 15% in phase 4. Normal Thr diets were formulated to contain 61, 62, 63, and 65% SID Thr:Lys ratios for the four dietary phases, respectively. High Thr diets had SID Thr:Lys ratios of 67, 68, 69, and 72%, respectively. There were no interactions (P>0.10) observed in any phase or overall, between Thr level and inclusion of DDGS for ADG, ADFI, F/G, and BW. For the overall period (d 0 to 112), pigs fed diets without DDGS had increased (P<0.001) ADG and BW and reduced (P<0.001) ADFI leading to improved (P<0.001) F/G. There was no evidence for difference (P>0.10) between diets with or without the inclusion of DDGS when diets were formulated to normal or high SID Thr:Lys ratio. In summary, the addition of high levels of DDGS reduced ADG and increased ADFI, which resulted in poorer F/G and lower final BW, regardless of the dietary SID Thr:Lys level. Additional research should be conducted to evaluate the effect of high Thr:Lys levels when soluble fiber sources are included in finishing pig diets instead of an insoluble fiber source such as corn DDGS.
Keywords: finishing pig; growth; DDGS; threonine